Penerapan Peer Teaching dalam Upaya Peningkatan Kreatifitas Berfikir Siswa - Deddy Hendriady (Journal of Elementary Education Research, 2022)
This study aims to evaluate the implementation of peer teaching model in an effort to enhance creative thinking of sixth grade students in science subjects, particularly in the topic of puberty at SD Negeri Ciremai Giri, Kota Cirebon. This study uses a qualitative approach with data collection techniques through observation, documentation, and questionnaires on 36 students. The results show that the implementation of the peer teaching model is effective in enhancing students' creative thinking skills on the topic of puberty. The use of peer teaching model can improve students' creative thinking in problem solving, material explanation, as well as students' activity in the class. The conclusion of this study is that the peer teaching model can be an effective alternative in enhancing students' creative thinking in science subjects at SD level.